Women cotton farmers: Their perceptions and experiences with transgenic varieties: A case study for Colombia - Zambrano, Patricia; Maldonado, Jorge H.; Mendoza, Sandra L.; Ruiz, Lorena; Fonseca, Luz Amparo; Cardona, Iván (International Food Policy Research Institute, 2011)
This paper explores gender differences in cotton cultivation and looks into the perceptions and experiences of women and men with transgenic varieties. With few exceptions, researchers in the area of impact evaluation of crop biotechnology have only marginally included gender considerations in their work. This exploratory pilot study was developed in order to incorporate gender into our quantitative evaluation work. This study used a participatory and descriptive approach that allowed us to listen to women and men farmers' perceptions and insights. The project was conducted in the main cotton-producing regions of Colombia where a handful of transgenic varieties have been in the market for the past six years.